2005
DOI: 10.1111/j.1740-8709.2005.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutritional knowledge and child nutritional status in the Volta Region of Ghana

Abstract: The relationship between mother's nutritional knowledge, maternal education, and child nutritional status (weight-for-age) was the subject of investigation in this study. The data were collected in Ghana on 55 well nourished and 55 malnourished mother-child pairs. A questionnaire designed to collect data on mother's knowledge and practices related to child care and nutrition was administered to the mothers. Data on mother's demographic and socio-economic characteristics as well as child anthropometric data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 19 publications
11
65
2
3
Order By: Relevance
“…The similar observations reported from North African regions [8][9][10][11] , Southeast Asian [13][14][15] and Latin American countries (14). In a case-control study in Bangladesh, the maternal illiteracy was associated with a fourfold increase in the risk of severe acute malnutrition in their children [14] ; which is higher than the findings of the present study.…”
Section: Discussionsupporting
confidence: 86%
“…The similar observations reported from North African regions [8][9][10][11] , Southeast Asian [13][14][15] and Latin American countries (14). In a case-control study in Bangladesh, the maternal illiteracy was associated with a fourfold increase in the risk of severe acute malnutrition in their children [14] ; which is higher than the findings of the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Here, the respondents improved their practical knowledge, in terms of being better able to name foods rich in the respective nutrients. This is in accordance with studies which showed that practical nutrition knowledge played a greater role in the nutrition outcomes as compared to the education level of the mother [36,37].…”
Section: Discussionsupporting
confidence: 80%
“…Children whose mothers are illiterate were 4 fold at risk to have severe acute malnutrition as compared to those children have literate mothers. Similar findings were revealed at studies done in Shashogo Woreda, Southern Ethiopia [22], Gonder, Ethiopia [17], Oromia region, West Ethiopia [14], Somali Region, Ethiopia [12], in Ghana [24], Gambia and Nigeria [18], Bangladesh [25] and Granada, Nicaragua [26]. This could be due to illiterate mothers have less perception about the nutritional need of their children and most of them have poor socio-economic status.…”
Section: Discussionsupporting
confidence: 72%